A Case Study of English Affricate Consonants Realized by a Two- year-old Indonesian Child: A Case Study of English Affricate Consonants Realized by a Two- year-old Indonesian Child (e-Journal of Linguistics, 2020)
n English, the two affricate consonants are not owned by otherlanguages. They are [dʒ] a voiced affricate like in the wordjaguar, garage, and jeep, and [tʃ] a voiceless affricate like in theword chin, cheap, and check. These sounds are phoneticsequences consisting of a stop with a fricated release. For someEFL learners, especially children, producing those sounds aredifficult because they don’t have a similar or same sound in theirfirst or mother language like in Indonesian language. This study isaimed to explore the realization of English two affricateconsonants produced by a two-year-old Indonesian child whospeaks both English and Indonesian language. This qualitativecase study shows a significant result on the voiced and voicelesspost-alveolar consonant. The child couldn’t produce [dʒ] as in GAproduction in an initial sound of the word. She produced [j] soundinstead, but she could pronounce it if the sound is in the finalsound of the word. In contrast, she could pronounce [tʃ] as in GAproduction in both the initial and final sound of the word withease. This study contributes helping English teachers to teachtheir students, especially children in their golden age, topronounce English words and to contribute to the field ofphonetics and phonology, specifically in teaching Englishpronunciations to EFL learners.